Overview of a Lesson on Participation in the Happy Public-Organization Index Development Program by Holding Learning Exchange Workshops - ธรรมกุล ดร.ดวงเนตร; ประเสริฐสิน ดร.อัจศรา; ชื่นศิริมงคล ดร.จริยา; ครุฑกาศ ดร.ศิริพร (Journal of Food Health and Bioenvironmental Science, 2016)
The creation of happy public organizations is one of the key tasks of organizations’ executives. These follow-up lessons used mixed methodology. The instrumentation employed was composed of a questionnaire on opinions about participation in a Happy Public-Organization Index (HPI) development program. The questionnaire was examined for structural validity by three qualified experts with a value of IOC= 0.88. The accuracy of the questionnaire was examined by Cronbach’s Alpha Coefficient; a value of r = 0.75 was obtained. The guidelines for the group discussions were semi-structured interviews, recording field notes and After Action Review (AAR). Data was collected by employing in-depth interviews and group discussions with a sample group composed of 32 people from 19 hospitals under the Ministry of Public Health who were willing to attend the learning exchange workshop on 30 April-1 May 2015. The quantitative data was analyzed with basic statistics and the qualitative data was analyzed with content analysis. According to the findings, the overall opinion about participation in the activities in the Happy Public- Organization Index (HPI) development program was the highest (χ = 4.29, SD=.95). The individual opinions revealed every item to also be the highest. In other words, people remained interested in using the Happy Public-Organization Index (HPI) in the future. In addition, benefits were yielded by using the Happy Public-Organization Index (HPI) in that lessons learned were exchanged. Thus, the course developed happiness creators for hospitals was beneficial in designing the creation of hospital happiness, including a view of applicable examples of other hospitals in creating happiness and satisfaction in having participated in the activities, which was the highest (χ= 4.19, 4.00, 4.47, 4.23, 4.46, 4.22, SD=.93, .99, .95, .92, .91, .94, respectively).